Valoración del riesgo de desarrollar Diabetes Mellitus tipo 2 mediante el Test de Findrisk en pacientes que acuden al Centro de Salud Universitario de Motupe - Lozano Ojeda, Andrea Beatriz (2023)
Diabetes mellitus is considered a metabolic pathology that intervenes with a high risk in people’s lives due to its period of intervenes with a high risk in people’s lives due to its period of evolution, the complications it entails, and the high mortality it causes, producing a predominant affectation in the health of human beings, The present research was carried out at the University Health Center of Motupe, with the purpose of determining by means of the Findrisk test the level of risk of developing Type 2 diabetes, as well as to evaluate according to sex and stablish the main risk components related to the development of this disease. A descriptive study with a quantitative approach, prospective vision and cross-sectional cut was carried out with a sample of 342 inhabitants. According to the results obtained, 20.76% of the individuals have a significant risk of presenting diabetes mellitus. Likewise, it was evidenced that the risk was more evident in women with 70.76% of developing the pathology mentioned in comparison with men. The main modifiable risk factors that influence its appearance were: physical inactivity, overweight and obesity. On the other hand, the following factors could not be modified: sex, age range, family history of diabetes, consumption of antihypertensive drugs and history of hyperglycemia. Finally, a significant risk level of developing this pathology in patients attending the University Health Center of Motupe was determined, this is mainly due to the following factors involved in its presentation: age, lack of physical activity, overweight, obesity, inadequate dietary habits, hypertension and genetic factors, as a result of this reality, it is therefore essential to increase prevention efforts, with special emphasis on timely diagnosis and appropriate treatment.